Epidemiology of pharmaceutically treated depression and treatment resistant depression in Taiwan. (June 2017) - Fife, Daniel; Feng, Yu; Wang, Michael Yao-Hsien; Chang, Chee-Jen; Liu, Chia-Yih; Juang, Hsiao-Ting; Furnback, Wesley; Singh, Jaskaran; Wang, Bruce
Abstract: Epidemiologic data on treatment resistant depression (TRD) in Asia-Pacific countries are limited. We estimated the incidence of TRD in Taiwan using a cohort of 704, 265 adults randomly sampled from Taiwan's National Health Insurance Research database for 2005. TRD was defined as a patient having pharmaceutically treated depression (PTD) not adequately responding to 2 antidepressant (AD) regimens, i.e., AD regimens that were followed by other AD regimens. Among 2751 PTD subjects, 576 (20.94%, 95% CI: 19.46, 22.49) developed TRD, a proportion similar to that in North American studies. TRD incidence was 0.82 (95% CI: 0.75, 0.89) cases /1000 population in 2005, increased with age, and was higher in females than in males. SSRI's were the most frequently used ADs. Augmentation with antipsychotics was common. The median time from PTD onset (first AD medication) to TRD onset was 416 days but psychiatrists practicing in Taiwan indicated they would switch within <=3 months if an AD medication was not effective. We therefore repeated the analysis with a 6 months cap on time from onset of PTD to TRD. In this supplemental, post-hoc, analysis, 68 PTD subjects, 2.47%, (95% CI: 1.94, 3.10) developed TRD; i.e., 0.10 (95% CI: 0.08, 0.12) incident cases/1000 population. Highlights: Treatment resistant depression (TRD) was defined by 2 failed antidepressant regimens. TRD developed in 21% of depressed subjects. The median time from depression onset to TRD onset was 14 months. Ineffective antidepressant regimens would normally be changed within 3 months. Only 2.5% of depressed patients develop met the criteria for TRD within 6 months.